SARS-CoV-2 Infects Human Engineered Heart Tissues and Models COVID-19 Myocarditis - Bailey, Adam L.; Dmytrenko, Oleksandr; Greenberg, Lina; Bredemeyer, Andrea L.; Ma, Pan; Liu, Jing; Penna, Vinay; Winkler, Emma S.; Sviben, Sanja; Brooks, Erin; Nair, Ajith P.; Heck, Kent A.; et al. (JACC. Basic to translational science, 2021)
[Display omitted] •SARS-CoV-2 directly infects cardiomyocytes in patients with COVID-19 myocarditis and does not infect cardiac macrophages, fibroblasts, or endothelial cells.•COVID-19 myocarditis is characterized by a myeloid-rich inflammatory infiltrate.•SARS-CoV-2 infects cardiomyocytes through an ACE2 and endosomal cysteine protease dependent pathway.•Infection of hPSC-derived cardiomyocytes and engineered heart tissues show that cytokine production, sarcomere disassembly, and cell death were a direct consequence of cardiomyocyte infection.•SARS-CoV-2 reduces cardiomyocyte contractility through sarcomere breakdown and cardiomyocyte cell death. There is ongoing debate as to whether cardiac complications of coronavirus disease-2019 (COVID-19) result from myocardial viral infection or are secondary to systemic inflammation and/or thrombosis. We provide evidence that cardiomyocytes are infected in patients with COVID-19 myocarditis and are susceptible to severe acute respiratory syndrome coronavirus 2. We establish an engineered heart tissue model of COVID-19 myocardial pathology, define mechanisms of viral pathogenesis, and demonstrate that cardiomyocyte severe acute respiratory syndrome coronavirus 2 infection results in contractile deficits, cytokine production, sarcomere disassembly, and cell death. These findings implicate direct infection of cardiomyocytes in the pathogenesis of COVID-19 myocardial pathology and provides a model system to study this emerging disease.